PLANNING FOR EXPORT AFTER THE PANDEMIC - JONATHAN REUVID (University OF BUCKINGHAM, 2020)
While the COVID-19 pandemic has brought the global economy to a standstill, businesses in the UK will need to be ready for exporting once the crisis is over. This downloaded text and reports provide advice on key strategic priorities, documentation, practices and regulations, as well as crucial trade data on key countries.